Clinical features of children, adolescents, and adults with coexisting hypermobility syndromes and von Willebrand disease. Issue 12 (7th August 2018) - Hall, Sarah A.; Meier, Emily Riehm; Gupta, Sweta; Nakar, Charles; Rampersad, Angeli; Bakeer, Nihal; Hardesty, Brandon; Kumar, Manjusha
Abstract: We present five patients with coexistent von Willebrand disease (VWD) and Ehlers‐Danlos syndrome and 21 with VWD and joint hypermobility. Females outnumbered males ten to three, Beighton scores were documented in 58% (15 of 26 patients), and several patients experienced moderately severe bleeding. We believe coexistent hypermobility disorder with VWD potentially affects bleeding severity and want to raise awareness among hematologists. Evaluation by geneticists is recommended because of the varying complexities observed across the disease spectrum, and the availability of new genetic tests should lead to more accurate diagnoses for the various hypermobility disorders.